Attenuated initial serum ferritin concentration in critically ill coronavirus disease 2019 geriatric patients with comorbid psychiatric conditions - Abulseoud, Osama A.; Yehia, Asmaa; Egol, Claudine J.; Nettey, Victor N.; Aly, Mohamed; Qu, Yihuai; Skolnik, Aaron B.; Grill, Marie F.; Sen, Ayan; Schneekloth, Terry D. (Frontiers in Psychiatry, 2022)
We examined the effects of psychiatric comorbidity, sex, and ICU admission on serum ferritin concentration in 628 elderly patients (79.7±8.5 years) with positive SARS-CoV-2 PCR test. Hospitalization was required in 96% of patients and 17% required ICU admission. Patients with COVID-19 and psychiatric comorbidities (n=212) compared to patients without psychiatric comorbidities (n=416) had significantly lower ferritin concentration (570.4±900.1vs.744.1±965, P=0.029), a greater incidence of delirium (22.6% vs. 14.4%, P=0.013) and higher mortality (35.3% vs. 27.6%, P=0.015). Furthermore, we found significant effects for sex (P=0.002) and ICU admission (P=0.007). Among patients without comorbid psychiatric conditions, males had significantly higher ferritin compared to females (1098.3±78.4vs.651.5±94.4, P<0.001). ICU patients without comorbid psychiatric conditions had significantly higher serum ferritin compared to ICU patients with comorbid psychiatric conditions: (1126.6±110.7vs.668.6±156.5, P<0.001). Our results suggest that the presence of comorbid psychiatric conditions in elderly patients with COVID-19 is associated with higher rates of delirium and mortality and lower ferritin levels during severe illness. Whether high serum ferritin is protective during severe infection requires further investigation.